Growth Rate and Feed Conversion Rate of Ostriches Fed Ration with or Without Grit in Botswana - Waugh, E.E.; Aganga, A.A.; Seabo, D.; Omphile, U.J.; Tsopito, C.M. (International Journal of Poultry Science, 2006)
The objectives of this study were to investigate the effect of grit on the growth rate, feed intake and feed conversion efficiency of ostrich chicks which were given grit and those not provided with grit. Six female and four male ostrich chicks aged nine (9) weeks were randomly assigned into two feeding groups using completely randomized experimental design. In each feeding group there were five young birds raised in a pen. All the young birds were fed with ostrich grower`s mash and water ad libitum. One group had access to grit during the study while other group did not. At week 18 weeks feed given to both groups of young ostriches and leftover were weighed on daily basis. Body weights were recorded on a monthly basis throughout the study. Average daily feed intake and average daily weight gain were determined. Feed conversion efficiency was calculated using average daily feed intake and average daily weight gain. The data was analyzed using Student - t analysis at P< 0.05. Average daily weight gain was higher (0.38 ± 0.03 kg/d) in ostrich chicks that had access to grit as compared to ostrich chicks (0.37 ± 0.04kg/d) that had no access to grit. Average daily feed (dry matter) intake was higher (1.95 ±0.27kg/d) in ostriches that had no access to grit than those (1.94 ± 0.20kg/d) access to grit. Feed conversion efficiency of ostriches with access to grit was higher (5.11 ± 0.93) than those (5.27 ± 1.30) without access to grit. Giving grit to young ostriches should be recommended both to improve growth rate and feed conversion efficiency and to reduce feed intake.